Gender Differences in Emotional Intelligence in Adolescence - Kochetova Y.A.,; Klimakova M.V., (Психолого-педагогические исследования)
The article presents the analysis of gender differences in emotional intelligence (EQ) in adolescence. The hypothesis was based on the assumption that there are gender differences in EQ in adolescence. The research involved 111 15-16 years old students, 57 of whom were girls and 54 of whom were boys. An ascertaining experiment with using such measures as "EmIn" (D.V. Lyusin), method of "Assessment of EQ" (N. Hall) and "Diagnosis of gender identity" (S. Bem modificated by V. A. Labunskaya, M. V. Burakova) were taken as a method. As a result, the hypothesis was confirmed, the leading components of EQ for boys and for girls were brought out, the qualitative description of the structure of EQ was given. The research expants the notion of the specifics and gender differences in EQ in adolescence. The obtained data could be used in the age-psychological counseling, in correctional and developmental work with adolescents, and the recommendations for development of EQ could be formulated.